Implementasi Emergency Geriatric Assessment pada Pasien Lansia di Ruang Instalasi Gawat Darurat RSUD. Dr. R. Goeteng Taroenadibrata Purbalingga: Case Study - Emilia Eka Purti; Sidik Awaludin; Dani Tri Santosa (Journal of Bionursing, 2020)
Background. The higher number of morbidity and emergency department visits for persons aged 75 years compared with the people under 65 years were the basic reason needed for a multidimensional and rapid assessment in the emergency department. The Emergency Geriatric Assessment may effective to be used to identify geriatric problems in the emergency department. Methods. This kind of implementation was a case study. This implementation was done on July 11st - 17th, 2019. The total respondent of this implementation was 11 elderly. The criteria of the respondent were all of the elderly aged ≥60 years who were waiting for admission or being observed, and didn’t have an acute stroke, an acute myocardial infarction, or was awaiting surgical intervention and admission. The instrument used a questionnaire named Emergency Geriatric Assessment, which consisted of twenty-two possible problems in the elderly. Results. The results of the Emergency Geriatric Assessment showed that the majority of the elderlies were 60-74 years, were male, had a medical decisions and had an ability to care for self by themselves. The majority of the identified problems were dementia, sleep, polypharmacy, pain, nutrition, use of medical resources, caregiver, family meeting, need for comfortable care, and long term bedridden. Conclusion. The Emergency Geriatric Assessment was effective to be used for identifying at least two geriatric problems in elderly, in order to help emergency department physicians to manage such patients.